Osserda or perhaps Olerda, a possible toponym in the Irulegi inscription / Osserda o acaso Olerda, posible topónimo en la inscripción de Irulegi - Gorrochategui, Joaquín (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2025)
This brief note offers an interpretation as a toponym of the term oTiŕtan attested in the recently found Palaeo-Hispanic inscription from the hillfort of Irulegi (Aranguren, Navarre), which is justified both by its lexical structure and by the identification of a suffix of locative value. The value of the sign T, known to date on several Vasconic coins, is under discussion, suggesting the possibility that it corresponds to the digraph -lt- common in Iberian epigraphy. In short, it would be a toponym of Iberian origin with Basque inflectional morphology.